Tumor volume change at radiation boost planning to estimate the response to chemoradiotherapy in stage III unresectable NSCLC (TORCH): a multicenter retrospective observational study - Trommer, Simon; Müller, Jörg Andreas; Oertel, Michael; Ehret, Felix; Roohani, Siyer; Ha, Hai Minh; Ha, Quynh Ngo; Hering, Kathrin; Nägler, Franziska; Lange, Tim; Mäurer, Matthias; Weissmann, Thomas; et al. (Strahlentherapie und Onkologie, 2025)
Background: Progression-free (PFS) and overall survival (OS) in UICC stage III non-small cell lung cancer (NSCLC) after definitive concurrent chemoradiotherapy (CRT) can be increased with consolidating immunotherapy. Recent studies have shown a strong predictive value of gross tumor volume (GTV) changes during CRT on OS. The TORCH trial investigated the prognostic impact of GTV changes during CRT as a predictor for a response to immunotherapy. Methods: This retrospective non-interventional observational multicenter trial included n = 203 patients from 10 German university centers for radiation oncology with confirmed inoperable NSCLC in UICC stage III A–C. Patients had received CRT between 2015 and 2023 as a curative-intent treatment approach. Patient and tumor characteristics were collected anonymously via electronic case report forms. Initial GTVs before CRT (initial planning CT, GTV1) and at 40–50 Gy (re-planning CT for radiation boost, GTV2) were delineated. Absolute and relative GTV changes before/during CRT were correlated with OS to predict the response to CRT with sequential immunotherapy. Hazard ratios (HR) of survival analyses were estimated using adjusted Cox regression models. Results: The mean GTV1 before radiation therapy (RT) was 145.29 ml with the 25th, 50th, and 75th percentiles being 61.36 ml, 145.29 ml, and 204.93 ml, respectively. Before initiation of the radiation boost, the mean GTV2 was 99.58 ml, with the 25th, 50th, and 75th percentiles at 32.93 ml, 70.45 ml, and 126.85 ml. The HR for the impact of GTV1 on survival was 0.99 per ml (95% confidence interval [CI] 0.99–1.00; p = 0.49). For the absolute volume change between GTV1 and GTV2, the HR was 1.004 per ml (95% CI 0.997–1.011; p = 0.26). In a subgroup analysis of patients who were treated with durvalumab, absolute volume changes between GTV1 and GTV2 were associated with longer OS (HR = 0.955 per ml; 95% CI 0.916–0.996; p = 0.03). Overall, durvalumab treatment was positively associated with OS, demonstrating an HR of 0.454 (95% CI 0.209–0.990; p = 0.047). Conclusion: Pretreatment GTV and absolute GTV volume changes did not significantly correlate with OS. However, the absolute volume change between the pretreatment and replanning GTV was associated with longer OS in patients treated with durvalumab. Histological subtype, grading, UICC stage, age at onset, pulmonary comorbidities, and smoking status had no significant association with OS. Durvalumab treatment was associated with improved OS.
CRIS-Team Scopus Importer:2025-03-21
Keywords: Durvalumab; Gross tumor volume; Immunotherapy; Non-small cell lung cancer; Stage III lung cancer